2019
DOI: 10.1080/03069885.2019.1580676
|View full text |Cite
|
Sign up to set email alerts
|

SMS counselling at a child helpline: counsellor strategies, children’s stressors and well-being

Abstract: Providing helpline services to children via texting (i.e. Short Message Service or SMS) is being used increasingly. However, little is known about the quality of SMS counselling and its effect on the service users. Through a quantitative content analysis of 448 SMS sessions at the Danish child helpline, we studied counsellor behaviour and session impact. We found higher levels of children's well-being and empowerment after contacting the service. Multiple regression models showed that a positive impact of coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Some research has argued that due to anonymity and the loss of non-verbal communication, the therapeutic relationship cannot develop as comprehensively, but the same study found working alliance scores were higher in the online therapy sample. 30 Contextually, adolescents prefer to go online for therapy due to the perceived anonymity and as stigma may be decreased, 32,35 although there remains discrepancy across services as to whether crisis services should be contacted if significant risk is disclosed. [36][37][38] The anonymity of online therapy has been associated with greater self-disclosure compared to face-to-face therapy, with service users being more comfortable to discuss a range of topics.…”
Section: Introductionmentioning
confidence: 99%
“…Some research has argued that due to anonymity and the loss of non-verbal communication, the therapeutic relationship cannot develop as comprehensively, but the same study found working alliance scores were higher in the online therapy sample. 30 Contextually, adolescents prefer to go online for therapy due to the perceived anonymity and as stigma may be decreased, 32,35 although there remains discrepancy across services as to whether crisis services should be contacted if significant risk is disclosed. [36][37][38] The anonymity of online therapy has been associated with greater self-disclosure compared to face-to-face therapy, with service users being more comfortable to discuss a range of topics.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is part of a larger research project looking at the general effects of counselor behavior on children contacting a child helpline via texting (Jensen, Sindahl, & Wistoft, ; Sindahl, Fukkink, & Helles, ; Sindahl & van Dolen, ). The aims of this study are to determine (1) how children and youth contacting a child helpline with suicide ideation differ from children and youth discussing other topics; (2) whether text messaging helps children and young people with suicide ideation; and (3) which counselor behaviors are more effective for helping children with suicide ideation via texting.…”
mentioning
confidence: 99%
“…This suggests that the influence of the emotional support partner effect is not stronger for volunteers with a higher service-offering adaptiveness disposition. Emotional support is the most beneficial type of support for uncontrollable problems (Cutrona, 1990), which are the types of problems most frequently discussed at child helplines (Sindahl et al, 2019). Child helpline volunteers are trained to give emotional support for these problems through active listening and providing empathy (Sindahl, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…eating disorders or friendships), instrumental support is advised, whereas emotional support is better suited for problems out of the child's control (e.g. abuse or parents arguing) (Cutrona, 1990;Rains et al, 2017;Sindahl et al, 2019;Van Dolen and Weinberg, 2017). It is up to volunteers to determine how much of each type of support to give to each child (Gilat and Rosenau, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation